Is There an Association Between Untreated Hearing Loss and Psychosocial Outcomes? - Jayakody, Dona M. P.; Wishart, Justin; Stegeman, Inge; Eikelboom, Robert; Moyle, Thomas C.; Yiannos, Jessica M.; Goodman-Simpson, Jack James; Almeida, Osvaldo P. (Frontiers in Aging Neuroscience, 2022)
Objective: Age-related hearing loss is one of the leading causes of disability in older adults. This cross-sectional study investigated the association between untreated hearing loss, social (perception of quality and quantity of social network) and emotional loneliness (perception of limited emotional support), social isolation (size of the social network), social support (actual or perceived availability of resources from the social network) and psychological discomfort (depression, anxiety and stress) in older adults. Study design: Cross-sectional study design. Methods: A total of 202 community derived sample of volunteers, age range 40-89 years, mean age (M) = 65.3 + 11.0 years were recruited. Of these 115 were females (M =63.2 + 12.0 years) and 87 were males (M = 68.2 + 8.9 years). All participants completed a hearing assessment, social interaction and support questionnaire and a social and emotional loneliness questionnaire. Results: Hearing loss significantly contributed to both moderate (P <.001, B (95% CI): 0.01(0.99-1.02) and intense levels (P <0.001, 0.02 (1.00-1.04)) of emotional loneliness. Depression was significantly associated with satisfaction with social support (P <0.001; -0.17(-0.23- -0.11)), social interaction (P = 0.01; -0.07 -0.12- -0.01)), and moderate (P <0.001;0.31(1.22-1.53)) and intense (P <0.001;0.29 (1.20-1.50)) levels of emotional loneliness and intense levels of social loneliness (P = 0.01;0.12 (1.05-1.21). Conclusion: Untreated hearing loss significantly increases the odds of being emotionally lonely. Depression significantly contributes to social and emotional loneliness, satisfaction with social support and social loneliness. Given the higher prevalence of loneliness and psychological discomfort and their associations with untreated hearing loss, hearing-impaired older adults are at significant risk of developing loneliness and psychological discomfort. Therefore, hearing health professionals should be aware of the psychosocial burden that may accompany hearing loss, in order to provide appropriate advice and support.